The Role of Carbon Pricing in Accelerating Energy Transition: A Case Study of Indonesia's Industrial Processes and Product Use (IPPU) Sector - Alwaaritsy, Nurin; Romadani, Arista (Indonesian Journal of Energy, 2025)
Carbon pricing serves as an effective economic instrument to mitigate greenhouse gas emissions while fostering investment in renewable energy by reducing dependence on fossil fuels. This study examines the development of carbon pricing policies to accelerate the energy transition, focusing on the Industrial Processes and Product Use (IPPU) sector. The proposed scheme is based on the Emissions Trading Scheme (ETS), tailored to local regulations and industrial capacities. This research employs a systematic review and content analysis of successfully implemented carbon pricing policies in various countries. While carbon pricing has been applied in the energy and forestry sectors, existing studies often lack specificity regarding emission thresholds or quantified carbon values across different emission sources. The IPPU sector, despite being a significant emitter, remains underrepresented in current policy design and academic literature. The findings indicate that carbon commercialisation supports renewable energy transition projects and increases investment in the electricity sector. This study proposes a carbon credit scheme tailored to the Indonesian wood industry (referred to as Industry X), which has begun integrating biomass and bioenergy to compensate for fossil-based emissions. The novelty of this study lies in its targeted focus on the IPPU sector and the practical application of a carbon pricing framework for industrial decarbonisation. The results suggest that integrating carbon pricing with fiscal incentives and energy regulations enhances industrial competitiveness in transitioning to clean energy. This study provides policy recommendations to improve carbon pricing mechanisms, supporting renewable energy investment and sustainable industrial transformation.